2017
DOI: 10.1504/ijpm.2017.080919
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the barriers of supplier development using fuzzy AHP approach

Abstract: Abstract:The objective of this study is to identify and prioritise the supplier development barriers (SDBs). The SDBs were identified through literature review and categorised into six different levels namely strategic, mutual trust, supplier reliability and capability, integrative efforts and sharing, buyer reliability and capability and investment based on expert opinion. A fuzzy AHP approach has been used to prioritise SDBs. The expert's opinion was taken to identify perceptions of the significant SDBs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Sahu et al (2017) has very well highlighted the efficacy of the FAHP method and proposed to use the method in the selection of third-party logistics network. Dalvi and Kant (2017) used the FAHP method for ranking the barriers of supplier development. Sunil Kumar and Routroy (2017) used the FAHP method along with interpretive structural modeling technique to analyze the impediments to the supplier development programs.…”
Section: Methodology Adopted For Measuring the Interdependencies Of Psesmentioning
confidence: 99%
“…Sahu et al (2017) has very well highlighted the efficacy of the FAHP method and proposed to use the method in the selection of third-party logistics network. Dalvi and Kant (2017) used the FAHP method for ranking the barriers of supplier development. Sunil Kumar and Routroy (2017) used the FAHP method along with interpretive structural modeling technique to analyze the impediments to the supplier development programs.…”
Section: Methodology Adopted For Measuring the Interdependencies Of Psesmentioning
confidence: 99%
“…Hence, there is stringent need to study and prioritize these barriers. High investment and implementation cost (Raj et al ., 2019; Kamble et al ., 2018; Aggarwal et al ., 2019; Yadav and Desai, 2017; Campos, 2013); employee fear and resistance to change (Moeuf et al ., 2019; Aggarwal et al ., 2019; Khan and Haleem, 2015; Yadav et al ., 2018; McLean and Antony, 2014), lack of top management commitment (Dalvi and Kant, 2017; Yadav and Desai, 2017; Gijo and Antony, 2014; Sevinc et al ., 2018; Rafique et al ., 2016), unavailability of skilled manpower and need for enhanced skills (Khanzode et al ., 2020; Saniuk and Grabowska, 2020; Nagy et al ., 2018) and other listed in Table 1 are identified as barriers through literature search and with the opinion of the experts from the selected domain. After going through the review of the existing literature, it is perceived that several studies had analyzed LSS barriers and their contextual relationships, but no such effort is testified in these potential barriers in view of Industry 4.0.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers adopted the FAHP over method over AHP for solving various supplier research problems and reported improved decision making. The said research problems include but not limited to evaluating the risk of green components (Hu et al, 2009); supplier selection and evaluation (Alinezad et al, 2013); supplier evaluation and ranking (Tadić et al, 2014); supplier segmentation (Lo and Sudjatmika, 2016); analysing the barriers to supplier development (Dalvi and Kant, 2017); The procedural steps followed for determining the relative importance of PSEs in terms of weights.…”
Section: Fuzzy Analytic Hierarchy Process For Screening the Psesmentioning
confidence: 99%